Gerstmann's syndrome. Issue 847 (May 1996) - Sukumar, S.; Ferguson, G. C.
Abstract : Although Gerstmann's syndrome has been well documented since it was characterised in the latter half of last century, there has not been much literature on it in the last few years. We present a classical case in a patient who was admitted into hospital for an unrelated problem. We conclude that clinical examination still has a valuable role in neurology, despite the availability of excellent imaging techniques.